Педагогічні умови формування у старших дошкільників толерантного ставлення до дітей з особливими освітніми потребами - Кононенко, Олексій Леонідович (My University, 2024)
У роботі представлено результати дослідження проблеми формування у старших дошкільників толерантного ставлення до дітей з особливими освітніми потребами. Проаналізовано структуру та сутність поняття «толерантне ставлення». Охарактеризовано дітей з особливими освітніми потребами у інклюзивному середовищі закладу дошкільної освіти. Визначено особливості формування толерантного ставлення у дітей старшого дошкільного віку. Представлено результати дослідження рівня сформованості у старших дошкільників толерантного ставлення до дітей з особливими освітніми потребами. Визначено педагогічні умови та систему формування у старших дошкільників толерантного ставлення до дітей з особливими освітніми потребами. Розроблено методичні рекомендації для вихователів і батьків.
Kononenko O. L. Pedagogical conditions for the formation of a tolerant attitude towards children with special educational needs in older preschoolers. – Manuscript. Qualification work for the degree of "master" in the specialty 012 Preschool education. – Nizhyn Mykola Gogol State University. – Nizhyn, 2024. The work presents the results of a study of the problem of the formation of a tolerant attitude towards children with special educational needs in older preschoolers. The structure and essence of the concept of “tolerant attitude” are analyzed. Children with special educational needs in the inclusive environment of a preschool educational institution are characterized. The features of the formation of a tolerant attitude in older preschool children are determined. The results of a study of the level of formation of a tolerant attitude towards children with special educational needs in older preschoolers are presented. Pedagogical conditions and a system for forming a tolerant attitude towards children with special educational needs in older preschoolers have been determined. Methodological recommendations for educators and parents have been developed. Keywords: preschool education, older preschool age, inclusive education, child with special educational needs, tolerance, tolerant attitude
Keywords: інклюзивна освіта; дитина з особливими освітніми потребами; толерантність; толерантне ставлення; старший дошкільний вік; дошкільна освіта